KOMUNIKASI KELOMPOK PADA KOMUNITAS FAKTABAHASA (STUDI KASUS PADA KEGIATAN BELAJAR MENGAJAR BAHASA ASING DI KOMUNITAS FAKTA BAHASA BANDUNG) - Nova Aprilla; Arie Prasetio (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
The study, titled Group Communications in Community Faktabahasa (Case Study on Teaching and Learning Foreign Languages in Community Faktabahasa Bandung) to find out how the activities of group communication in teaching and learning foreign languages in community Faktabahasa Bandung and communication interactions between the tutors with the participants in the community Faktabahasa Bandung , The method used in this study is a qualitative method using descriptive case study. As well as the technique of collecting data includes in-depth interviews, observation, and documentation. Informants consisted of seven people. The results of this research are activities of group communication that occurs not only learn a foreign language but also learn the culture, consisting of activities their internalization (introduction), learning foreign languages (clubbing) with storytelling, games, singing, watching videos and movies, sharing and test (test) to describe the function of group communication. The interaction communication between the tutor with the participants is two-way communication involving verbal and nonverbal communication with the atmosphere of teaching and learning activities that take place informal, relaxed, warm, intimate and conducive.